Praktik Politik Uang Pada Pemilihan Kepala Daerah DKI Jakarta Tahun 2024: Studi Komparasi Kota Administrasi Jakarta Pusat dan Jakarta Selatan - Mohammad Reyhan Ardhito Nugroho; Nur Hidayat Sardini (Journal of Politic and Government Studies, 2026)
This study aims to analyse the dynamics of money politics practices and evaluate the effectiveness of prevention efforts during the 2024 Jakarta Regional Head Election (Pilkada) through a comparative study between the Administrative Cities of Central Jakarta and South Jakarta. Employing a qualitative method that integrates the Patronage-Clientelism theory, George C. Edwards III's Policy Implementation model, and a cultural approach, this research reveals that the modus operandi of money politics is highly adaptive to the local socio-cultural ecosystem. In the communal setting of Central Jakarta, the practice operates conventionally through